Structure–activity relationship of Cu-based catalysts for the highly efficient CO2 electrochemical reduction reaction - An, Runzhi; Chen, Xuanqi; Fang, Qi; Meng, Yuxiao; Li, Xi; Cao, Yongyong (Frontiers in Chemistry, 2023)
Electrocatalytic carbon dioxide reduction (CO2RR) is a relatively feasible method to reduce the atmospheric concentration of CO2. Although a series of metal-based catalysts have gained interest for CO2RR, it is still a great challenge to understand the structure–activity relationship for Cu-based catalysts. Herein, three Cu-based catalysts with different sizes and compositions (Cu@CNTs, Cu4@CNTs and CuNi3@CNTs) were designed to explore this relationship by density functional theory (DFT). The calculation results show that the degree of activation of the CO2 molecule on CuNi3@CNTs is higher than that of the Cu@CNTs, Cu4@CNTs. The methane (CH4) molecule is produced both on the Cu@CNTs and CuNi3@CNTs, while carbon monoxide (CO) is synthesized on Cu4@CNTs. The Cu@CNTs shows higher activity for CH4 production with a low overpotential of 0.36 V compared to CuNi3@CNTs (0.60 V), meanwhile the formation of *CHO is considered as the potential-determining step (PDS). Besides, the overpotential value only is 0.02 V for *CO formation on the Cu4@CNTs and formation of *COOH is the PDS. The limiting potential difference analysis with the hydrogen evolution reaction (HER) indicates that the Cu@CNTs exhibited the highest selectivity of CH4 among the three catalysts. Therefore, the sizes and compositions of Cu-based catalysts have great influences on activity and selectivity for CO2RR. This study provides an innovative insight into the theoretical explanation of the origin of the size and compositions effect, which are beneficial to the design of highly efficient electrocatalysts.